Human Autonomy and Divine Sovereignty: Negotiating Moral Freedom and Predestination in the Qur’an - Fakhri Afif; Irma Riyani (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2025)
This article pursues a philosophical reading of the Qur’an’s moral discourse on human freedom and divine sovereignty. Through an ethical close reading of Qur’anic verses and a semantic-conceptual analysis of mashī’ah, istiṭā‘ah, mas’ūliyyah, qadr, qaḍā’, and ‘adl, the study brings the philosophical category of relational freedom as a heuristic to the text, demonstrating that the Qur’an’s conceptual architecture actively enriches it. Methodologically, the inquiry draws on Abou El Fadl’s negotiative hermeneutics to navigate the author-text-reader dialectic and to assess the ethical stakes of competing interpretations. The findings establish that the Qur’an presupposes genuine moral agency through its idioms of non-coercion, taklīf, ḥisāb, and the moral evaluation of intention, while situating this agency within a divinely ordered structure of measure and decree grounded in ‘adl. Qadr is construed as a principle of causal measurability, and qaḍā’ as the moment of decisive actualization. The reading rejects predestination as a moral alibi while refusing to inflate human agency into a sovereignty that fractures the tawḥīdic horizon. This study contributes a philosophically rigorous framework for reading Qur’anic moral theology beyond the fatalism-autonomy impasse, and opens a constructive dialogue between Islamic moral thought and contemporary philosophy of agency that neither domesticates the Qur’anic account nor insulates it from critical engagement.